Comprehensive assessment of power quality in a low-voltage node with distributed generation and energy storage: evidence from field monitoring - Raichenko, A. (Energy and Automation, 2025)
The objective of this study is to conduct a comprehensive assessment of power quality parameters in a low-voltage node incorporating photovoltaic modules and an energy storage system, based on long-term field monitoring. The methodology involved analyzing time series of voltages, currents, active power, power factor, and total harmonic distortion recorded with a 15-minute resolution during the period September 2024 – March 2025. Data were segmented according to import and export modes of energy flow, resampled, and subjected to event-based detection of intervals deviating from EN 50160 and IEEE 519 standards. The results demonstrated that voltage consistently remained within permissible limits, whereas approximately 81% of measurements indicated current harmonic distortion exceeding 5%. The absolute power factor was not lower than 0.9 in 90% of cases, but declined to 0.85–0.90 in nearly 10% of intervals, primarily due to harmonic distortion and reactive power exchange. Moreover, the analysis confirmed the high stiffness of the supply network, which accounts for the stability of voltage parameters despite pronounced current harmonics. The findings underline the necessity of implementing active or passive filtering measures to mitigate harmonic distortion and maintain power factor stability.Key words: power quality, harmonic distortion, power factor, grid stiffness, short-circuit capability, low-voltage networks, municipal facilities